Glycine-assisted enhancement of 1,4-beta-D-xylan xylanohydrolase activity at alkaline pH with a pH optimum shift - Vathipadiekal, Vinod; Verma, Anamika; Rao, Mala (Biological Chemistry, 2007)
This is the first report describing the enhancement of xylanase activity by the neutral amino acid glycine. Xylanase activity is increased seven-fold at alkaline pH in the presence of glycine and its pH optimum is shifted from pH 7 to 8 without using any protein engineering techniques. Analysis of the steady-state kinetics revealed that glycine in the reaction mixture increases the K-m and k(cat) values of the enzyme. Chemoaffinity labeling and studies using glycine esters indicate an involvement of the carboxylate ion of glycine in enhancing xylanase catalytic activity. A novel possible mechanism for the glycine-assisted catalytic action of xylanase is proposed.
Keywords: Enzyme catalysis; OPTA; Thermomonospora sp.; Xylanase

Molecular cloning, over expression, and activity studies of a peptidic HIV-1 protease inhibitor: designed synthetic gene to functional recombinant peptide - Vathipadiekal, Vinod; Umasankar, Perunthottathu K.; Patole, Milind S.; Rao, Mala (Peptides, 2010)
The aspartic protease inhibitor (ATBI) purified from a Bacillus sp. is a potent inhibitor of several proteases including recombinant HIV-1 protease, pepsin, and fungal aspartic protease. In this study, we report the cloning, and over expression of a synthetic gene coding for ATBI in Escherichia coli and establish a purification Protocol. The ATBI molecule consists of eleven amino acids and is peptidic in nature. We used the peptide sequence data of ATBI to synthesize complementary oligonucleotides, which were annealed and subsequently cloned in-frame with the gene for glutathione-S-transferase (GST). The expression of the resulting fusion protein was induced in E. coli BL21-A1 cells using arabinose. The recombinant peptide was Purified using a reduced glutathione column, and cleaved with Factor Xa to remove the GST tag. The resultant product was further purified to homogeneity using RP-HPLC. Mass spectroscopy analysis revealed that the purified peptide had a molecular weight of 1186 Da which matches the theoretical molecular weight of the amino acids present in the synthetic gene. The recombinant peptide was found to be active in vitro against HIV-1 protease, pepsin, and fungal aspartic protease. The protocol described in this study may be used to clone pharmaceutically important peptide molecules. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Gateway cloning; HIV-1 protease; inhibitor; Proteases; Synthetic gene